Develompment of PBL Worksheets of Environmental Changes Topic to Train the Critical Thinking Skills of 10th Grades High School Students - Fadiah, Nur; Ambarwati, Reni (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2024)
Student worksheets for environmental changes topic help students understand learning concepts and achieve learning goals in the new curriculum era. Apart from that, the worksheets was developed based on the phases of the Problem Based Learning) model which correlates with critical thinking skills as the basis for the ability to solve environmental changes problems. This research aims to produce PBL worksheets that are valid, practical and effective. This development research uses a 4D development model (define, design, develop, and disseminate), without disseminate stage. The validity of the student worksheets is reviewed based on validation results by topic expert lecturers and media experts. The practicality of the student worksheets was reviewed based on the responses of teachers (n=3) and students (n=20). The effectiveness of the student worksheets is reviewed based on student learning outcomes in the form of pre-test and post-test as well as the achievement of critical thinking indicators. Data was analyzed quantitatively descriptively. The research results show that the student worksheets developed is very valid with a validation score of 92.7%. The student worksheets developed was considered very practical with a teacher response practicality score of 92.6% and a student response practicality score of 96%. Apart from that, the student worksheets is considered very effective with an N gain score of 0.8 and a critical thinking indicator achievement score of 93.3%. Based on this, the student worksheets developed is very valid, practical and effective for use as teaching topic on environmental changes and for practicing critical thinking skills.